The justifiable strikes under The Industrial Relations Act a review / Mohd Rohaizad Rosli - Rosli, Mohd Rohaizad (Faculty of Law, 1987)
1984 was a crucial year for the Trade Union movement. The frequency and momentum of strikes increased. A large number of these strikes had political motives. In tune, the Trade Union Enactment was amended to provide for the registration of federations of Trade Unions and the restrictions of their memberships to trade unions whose members were employed in similar trade, occupations or industries. A state of emergency was declared on 16 June 1948 and it was to last until 1960. The post-independence government appeared sympathetic to Trade Unions and conc2rned with Industrial In 1963, confrontation was declared with Indonesia and racial riots led to a proclamation of Emergency in 1969. Therefore, strict legislative controls over the Trade Union movement have continued with a view of preventing them from being used for purposes which threaten internal security and economic development.